ENVIRONMENTAL SUSTAINABILITY AND LIVELIHOOD QUESTION THROUGH THE FOREST RIGHTS ACT, 2006 IN TRIPURA - Kalai, Gouri; Chakma, Bindu Ranjan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sustainable Forest Management (SFM) is now given top priority for ensuring environmental and social sustainability. As an approach of SFM, the Government of India enacted the Forest Rights Act of 2006 (FRA-2006). The Government of Tripura implemented the FRA, 2006 in 2008 and since then, it introduced and executed various schemes under the FRA, 2006 for social sustainability of the tribal forest dwellers. The paper studies the nature of implementation of the FRA, 2006 in Tripura from the perspective SFM. The study argues that albeit implementation of FRA, 2006 increased income and improved life styles of tribal household beneficiaries, yet due to encouragement of extensive rubber plantation (mono culture) under the implementation of FRA, 2006, it has questioned about environmental sustainability. However, the paper argues that the scope of SFM through the implementation of the FRA, 2006 is extensive if, despite high economic benefits, it can reduce the dependency among the beneficiaries upon rubber plantations and encourage shifting to various other economically and environmentally viable occupations.